Erythropoietin’s Therapeutic Value in Preventing Methotrexate’s Adverse Renal Effects (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: Methotrexate may cause problems with the kidneys. Nonetheless, erythropoietin’s advantageousextra-hematopoietic impact may protect against methotrexate-induced nephrotoxicity. Objectives: Clarifying theimpact of renoprotective erythropoietin on renofunctional and renomorphological aspects in adult male albino ratswill help determine its role in mitigating methotrexate-induced nephrotoxicity. Materials and Methods: 60 malealbino rats were used in the investigation, and they were divided equally into 3 groups. The control one receivednormal saline 2 times a week for 9 weeks at a dosage of 0.5 mg/kg body weight (BW). Group 2 received 0.5 mg/kgBW intraperitoneal injections of methotrexate hydrate twice a week for 9 weeks. Group 3 received methotrexatehydrate intraperitoneally for the same amount of time and at the same dosage as group 2, along with a onceweeklysubcutaneous injection (S.C) of 100 IU/kg recombinant human erythropoietin. Rats were slaughtered,renal sections were ready for histological analysis, and serum urea, creatinine, and albuminuria were determinedat the conclusion of the study. Results: The methotrexate-treated group showed significantly higher levels ofrenal function assessed chemicals with worsening histological renal alterations when compared to the control orthe methotrexate and erythropoietin co-treated group. The latter showed significantly improved microscopic renalalterations along with statistically significant reductions in the drug levels. Furthermore, there were negligiblestatistical differences in renal morphology and biochemistry between different groups. Conclusion: This studyfound that animals given with erythropoietin in addition to methotrexate provided a valuable and effectiveresistance against methotrexate-induced nephrotoxicity.